2017
DOI: 10.11606/s1518-8787.2017051006952
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade climática aumenta a morbimortalidade associada ao material particulado

Abstract: OBJECTIVE The objective of this study has been to analyze whether fine particulate matter (PM2.5), as well as its synergistic effect with maximum temperature, humidity, and seasons, is associated with morbidity and mortality from cardiovascular diseases.METHODS This is an ecological study of time series. We have used as outcomes the daily death and hospitalization records of adults aged 45 years and over from 2009 to 2011 of the municipalities of Cuiabá and Várzea Grande, State of Mato Grosso, Brazil. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
8
0
5
Order By: Relevance
“…e results in the present study differ from other studies that showed the relationship between PM 2.5 and the increased risk of hospitalization for cardiovascular disease in people over 60 years. e adverse effects of PM on hospitalizations for cardiovascular disease were correlated with the same day of pollutant increase (lag 0) and decreased the risk on subsequent days [27][28][29][30]. e present study also differs from the academic literature that shows an association between PM 2.5 and the increase in hospitalization for cardiorespiratory diseases [31][32][33].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…e results in the present study differ from other studies that showed the relationship between PM 2.5 and the increased risk of hospitalization for cardiovascular disease in people over 60 years. e adverse effects of PM on hospitalizations for cardiovascular disease were correlated with the same day of pollutant increase (lag 0) and decreased the risk on subsequent days [27][28][29][30]. e present study also differs from the academic literature that shows an association between PM 2.5 and the increase in hospitalization for cardiorespiratory diseases [31][32][33].…”
Section: Resultsmentioning
confidence: 63%
“…the physiological response to toxic agents, increasing individual vulnerability [30]. We could not find any scientific articles that could support our findings.…”
Section: E Scientific World Journalmentioning
confidence: 53%
“…Of the nine studies that evaluated CVD mortality [27,31,33,35,36,37,38,43,44], eight (91%) reported significant effects of long-term PM 2.5 exposure. Of these studies, six were conducted in China, and one study each was carried out in Mexico, India, and Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Relative risk percentage (% RR) and 95% confidence intervals (95%CI) for mortality due to cardiovascular diseases related to the linear increase of 1ºC in the maximum temperature by simple lag, according to socioeconomic status in the residential environment and proximity to vehicular traffic . Cuiabá and Várzea Grande, from 2009 to 2011. elemental carbon and sulfate 26 , O 3 27 and the concentration of semivolatile particles 23 .On the other hand, the synergistic effects between high temperatures and atmospheric pollutants, such as O 3 and PM, have been related to the increased risk of mortality due to CVDs 14,28 . Heat can overload the body's thermoregulation system and increase individual vulnerability to the effects of air pollutants 29 .…”
Section: Discussionmentioning
confidence: 99%